PERAN PEKERJA SOSIAL PADA DISABILITAS MENTAL MELALUI BIMBINGAN VOKASIONAL DI RUMAH PELAYANAN SOSIAL DISABILITAS MENTAL (RPSDM) “MARTANI” CILACAP - Galih Galih Fajar Fadillah; Innayah Nur Aini (Politeknik Kesejahteraan Sosial Bandung, 2023)
This study aims to describe the role of social workers as enablers in restoring the social functioning of beneficiaries through vocational guidance. The research method used is qualitative research with a case study approach which is a method used to describe more complete information, so that the resulting understanding of a case is studied more deeply. This study used a purposive sampling technique to determine the subject, namely two social workers. Data collection techniques were carried out by interviews, observation, and documentation. The results of the study show that the role of social workers is as an enabler in restoring beneficiary social functioning through vocational guidance, namely at the production stage where social workers facilitate education and provide group work techniques for beneficiary social interaction needs. Then, in the post-production stage, social workers play a role in maintaining relations with stakeholders, creating social shop innovations, involving beneficiaries in vocational activities outside the institution as a means of selling their work and to familiarize them with adapting to the wider community environment. As well as, distributing work to beneficiaries who are able to be employed.